D1.4 QA guidelines - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Schreier, Gunter; Lasaponara, Rosa (My University, 2016)
This document represents the Quality Assurance (QA) guidelines for the ATHENA project. The aim of this deliverable is to describe the mechanisms that will be used throughout the project in order to ensure the quality level of the project deliverables and the project outcomes. This document will also serve as a guide for the project coordinator, in order to be easy to identify important tasks and dependencies that are critical for the success of the project. This document will also serve as a detailed guide to the ATHENA consortium in order to establish effective cooperation within the consortium and ensure the highest level of quality of project documentation. This document should be used as a reference by the project coordinator and all project partners.
Keywords: Quality asssurance; ATHENA project; Quality level